Wielding the Double‐Edged Sword of Inflammation: Building Biomaterial‐Based Strategies for Immunomodulation in Ischemic Stroke Treatment. (25th February 2021) - Letko Khait, Nitzan; Ho, Eric; Shoichet, Molly S.
Abstract: Stroke is a leading cause of disability with no current treatment to regenerate lost brain tissue. Innovative preclinical and clinical trials have attempted to improve stroke recovery by promoting cell survival, downregulating astrogliosis and inflammation, and improving neurogenesis and angiogenesis; however, the complexity of stroke pathophysiology raises many challenges. Previous attempts to grossly inhibit the inflammatory reaction failed to improve stroke outcomes, prompting scientists to explore selective modulation rather than unbiased inhibition. Although experimental studies involving immunomodulation are successful, strategies have largely failed in the clinic. Some of these approaches are hindered by poor delivery efficiency or cell survival, challenges that could be at least partially overcome using biomaterials. Biomaterials may enhance immunomodulatory processes by improving drug and cell delivery to the injured tissue. Furthermore, the materials themselves can support healing and may be designed to act as immunomodulators, thereby contributing to tissue regeneration and endogenous repair processes. Described here are novel biomaterial‐based strategies to modulate the immune response after ischemic stroke, with an emphasis on extracellular matrix mimetics and hydrogels for local delivery of drugs and cells. Finally, a future perspective is described, highlighting the potential of these therapies to achieve clinical translation and improve patients' functional repair. Abstract : Immunomodulatory approaches for the treatment of ischemic stroke, though promising, continue to remain elusive to clinical translation. Here, it is discussed how innovative biomaterials, whether as scaffolds, hydrogels, and/or nanoparticles, are able to serve as both immunomodulatory agents and biomolecular delivery vehicles to treat the stroke‐injured brain.